Examining Biases in ABS-CBN Online News: A Framing Analysis of Reporting about President Ferdinand Marcos Jr. - Robiego, Jeanard Anthony M.; Talde, Danna Karyl Jane C. (OKARA: Jurnal Bahasa dan Sastra, 2024)
ABS-CBN, a leading media entity in the Philippines, has often found itself embroiled in controversies surrounding accusations of bias, particularly in its coverage of President Ferdinand "Bong-Bong" Marcos Jr., commonly known as BBM. Various entities have often criticized the media for exaggeration, framing, and misinformation, whereas others have praised the media for fulfilling an informative and educational function for the public. To address this dilemma, this study specifically examined its linguistic devices and language bias to discern patterns of news framing. This was done using the Linguistic Devices Analytical Framework, the Epistemological and Framing Bias Tool, and Goffman's Theory of Framing. Findings reveal the exclusion of the inclusive language 'we,' and language bias reveals linguistic devices, such as factive verbs, entailments, assertive verbs, subjective intensifiers, and one-sided terms. With the interplay of these outcomes, ABS-CBN headlines exhibit a combination of positive, negative, and neutral news coverage, which aligns with the norms of balanced reporting, essential for audiences to understand the story from various perspectives. Generally, findings reveal an impartial framing of news headlines. Future research may conduct a longitudinal study with a comprehensive dataset of news headlines to explore the media’s intentions revealed through framing strategies.